Alternativas de redes multimodais para o transporte público da Zona Oeste da Região Metropolitana de Fortaleza - Batista Filho, Jovino (2002)
This work presents an analysis of the impacts over the users resulting from different scenarios of modal integration in the public transport system, having as vase study the home-to-work moments in the west portion of Fortaleza´s Metropolitan Region. The following performance measures wereselected for a zonebased aggregated analysis: modal shift, fare cost, total travel time, as well as number and places of transfers. The network scenarios are modelled differently from the traditional way as the generalized cost functions are represented by link/mode combinations, making it possible to simultaneously model the madechoice and the assignment on uni- or multimodal paths of integrated public transit networks. The GIS-T (TransCAD 4.0) toll was used, allowing a more efficient representation of the network scenarios as well as treatment of the obtained results, making it easier the spatial analysis of the performance measures by user groups. The results of the case study analysis indicated that modal shifts are more sensitive to fare changes than to variations in the value of time and in the walking weight. It is believed that the adopted demand analysis methodology contributes to a better understanding of the factor which influence modal choice, increasing the chances of implementing successful actions on the public transport system.